RELATIONSHIP BETWEEN THE INTENSITY OF GLYCOLYSIS AND THE METASTATIC POTENTIAL OF CANCER CELLS - Hnatiuk , Solomia; Solyanik , Galyna (Collection of scientific papers «ΛΌГOΣ», 2023)
Despite significant advances in treatment methods and the development of new therapeutic drugs, cancer remains one of the most serious diseases. Anti-tumor therapy, particularly antimetastatic therapy, is still relevant. It is known that, compared with normal cells, cancer cells are characterized by an intensification of glycolysis and an increase in glucose uptake to ensure high proliferative activity. Meanwhile, the question of the relationship between the intensity of glycolysis and the metastatic potential of tumor cells remains open. Therefore, understanding the metabolic processes in metastatic cancer cells may lead to the development of new, more effective therapeutic methods.